UPAYA PENINGKATAN KEMAMPUAN APARATUR DESA DALAM PELAKSANAAN TUGAS ADMINISTRASI DI DESA LINGGANG AMER KECAMATAN LINGGANG BIGUNG KABUPATEN KUTAI BARAT - Kornelius Kornelius (ADMINISTRASI PUBLIK, 2019)
KORNELIUS, Thesis Title Efforts to Increase the Capability of Village Apparatus in the Implementation of Administrative Tasks in Linggang Amer Village, Linggang Bigung Sub-District, West Kutai Regency, Advisor I Mrs. Dra. H. Nanik Pujiastuti, M.Si and Ms. Raudah Mahmud, S.Ag, M.HI as II supervisors.The purpose of this paper is: 1. To find out about efforts to improve the ability of village officials in carrying out administrative tasks in Linggang Amer Village, Linggang Bigung Sub-District, West Kutai Regency. 2. To find out the inhibiting and supporting factors in carrying out government administrative duties in the village of Linggang Amer, Linggang Bigung District, West Kutai Regency.The results showed that the implementation of government duties in Linggang Amer Village, Linggang Bigung Subdistrict, West Kutai Regency in the process of administrative services to the community tended to be less than optimal, and would continue to be an evaluation of village government so that the services provided could be maximized.Efforts to Increase the Capacity of the Linggang Amer Village Apparatus in carrying out the administration in Linggang Amer Village, Linggang Bigung District, West Kutai Regency; 1. Development of apparatus discipline. 2. Education and training. Giving Work Motivation. Supporting factors and inhibiting factors, supporting factors in the form of hardware and software. While the inhibiting factor is the ability to measure knowing the skills of each apparatus, as well as difficulties in the operation of the application of village funds financial statements.